Writing Is Vision Is Sound Is Word: Surveillance Systems in Jeff VanderMeer’s Dead Astronauts - Sparks, Simone (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2026)
How can literary works recast visual models of surveillance systems when writing is itself a visual technology? Writing’s essential visual affordances mean that novels cannot claim to impart aesthetic experiences that inherently disrupt the surveillant knowledge regimes to which they are bound. Within this article, I outline recent scholarship that troubles this relationship. I compare literary representations of the surveillance state and surveillance resistance in Orwell’s Nineteen Eighty-Four (1949) to Jeff VanderMeer’s experimental, multimodal novel Dead Astronauts (2019). Nineteen Eighty-Four has long been considered outdated, in metaphor and systemic reality. But what more can one expect when the affordances of writing are left unraveled? Dead Astronauts is a text to which we might turn for this undoing. Visual knowledge is taken to task through its form—tactile and visual ways of reading are combined to render the novel’s multi-species dialogue around surveillance resistance. Dead Astronauts offers an updated aesthetic approach to how novels can, at the level of form, disrupt visual knowledge systems. It is because the novel experiments with the boundaries of written language that it manages to successfully voice critiques of racialized surveillance capitalism, ecological crisis, and the failure of anthropocentric priorities in resistance movements. An allegorical cast of non-human, chimeric characters are exploited by the novel’s formal structure, enacting surveillance capitalism’s extraction of data’s raw materials: mind, imagination, and future behavior. The novel’s form is a cipher that troubles whether a readerly interest in solution begets reward. Dead Astronauts shows that exemplary surveillance novels must do more than mirror the warping nature of a multisensory surveillance assemblage through traditional narrative. Multimodal novels that thoroughly metabolize algorithmic surveillance via the proximal dissection of language might recruit resistant, critical subjects, or readers who understand that visuality is a limited paradigm for perceiving a future whose face we increasingly fail to recognize.